Knowledge and use of emergency contraception among students of public secondary schools in Ilorin, Nigeria - Babatunde, Oluwole Adeyemi (Pan Afr Med J, 2016)
INTRODUCTION: Unintended pregnancy and unsafe abortion pose a major reproductive health challenge to adolescents. Emergency contraception is safe and effective in preventing unplanned pregnancy. The objective of this study was to assess the student's knowledge and use of emergency contraception. METHODS: This cross-sectional study was carried out in Ilorin, Nigeria, using multi-stage sampling method. Data was collected using pre-tested semi-structured self-administered questionnaire. Knowledge was scored and analysed. SPSS version 21.0 was used for data analysis. A p-value <0.05 was considered statistically significant. RESULTS: 27.8% of the respondents had good knowledge of emergency contraception. Majority of respondents (87.2%) had never used emergency contraception. Majority of those who had ever used emergency contraception (85.7%) used it incorrectly, using it more than 72 hours after sexual intercourse (p=0.928). CONCLUSION: Knowledge about Emergency contraception and prevalence of use were low. Contraceptive education should be introduced early in the school curriculum for adolescents.